A new species of the lichen genus Parmotrema from Argentina (Parmeliaceae, Ascomycota) - Michlig, Silvia Andrea; Ferraro, Lidia Itatí; Elix, John (Phytotaxa, 2014)
A new Parmotrema species, P. pseudoexquisitum, was found in Araucaria angustifolia forests in northeastern Argentina. It is characterized by a coriaceous thallus with very sparsely ciliate lobes, strictly marginal soralia with farinose to subgranular soredia, a white medulla and containing conalectoronic and subalectoronic acids in addition to alectoronic and α-collatolic acids. It is closely related to P. exquisitum, which differs in lacking marginal cilia, in having submarginal to laminal soralia with farinose soredia, and its medullar chemistry. This new species is described and illustrated in this paper. Comparisons with other sorediate Parmotrema species with medullary alectoronic acid are included.